Characterization of induced nanoplasmonic fields in time-resolved photoemission: A classical trajectory approach applied to gold nanospheres - Saydanzad, Erfan; Li, Jianxiong; Thumm, Uwe (My University, 2017)
Attosecond time-resolved spectroscopy has been shown to be a powerful method for examining the electronic dynamics in atoms, and this technique is now being transferred to the investigation of elastic and inelastic scattering during electron transport and collective electronic (plasmonic) effects in solids. By sampling over classical photoelectron trajectories, we simulated streaked photoelectron energy spectra as a function of the time delay between ionizing isolated attosecond extreme ultraviolet (XUV) pulses and assisting infrared or visible streaking laser pulses. Our calculations comprise a sequence of four steps: XUV excitation, electron transport in matter, escape from the surface, and propagation to the photoelectron detector. Based on numerical applications to gold nanospheres of 5- and 50-nm radius, we investigate streaked photoemission spectra with regard to (i) the nanoparticle's dielectric response to the electric field of the streaking laser pulse, (ii) relative contributions to photoelectron release from different locations on the surface and inside the nanoparticle, (iii) contributions of photoemission from the Fermi level only versus emission from the entire occupied conduction band, and (iv) their fidelity in imaging the spatiotemporal distribution of the induced plasmonic field near the particle's surface.
Keywords: Atomic & molecular processes in external fields; Dielectric properties; Metals; Photoemission